Local Genius dalam Drama dan Teater Putu Wijaya: Local Genius in Putu Wijaya's Drama and Theater - Purwanto Lephen; Senowarsito Senowarsito (Universitas Tidar, 2026)
This research aims to uncover and analyze the elements of local genius (local wisdom) that form the foundation of the aesthetics and philosophy in Putu Wijaya's dramaturgy. The research method employed is descriptive, with a hermeneutic approach, conducted through textual analysis of play scripts, such as Aduh, Edan, and Zero, as well as observation of the rehearsal process and performances of the